Grinding cereals and pulses in the Neolithic site of Kleitos: an experimental investigation of microconglomerate grinding equipment, final products and use wear - Chondrou, D.; Valamoti, S. M.; Procopiou, H.; Papadopoulou, L. (Journal of Greek Archaeology, 2018)
Stone grinding tools (i.e. querns or grinding stones / millstones / metates and handstones or grinders / upper milling stones / manos) constitute an important part of the material culture recovered in prehistoric excavations. These implements, as well as the technological category in which they are traditionally attributed, known by the generic term ‘ground stone tools’, and by the more recently proposed term ‘macrolithic tools’, received the interest they deserve not long ago, through specialized studies.